Stanje ekološkog maslinarstva u Europskoj uniji i Republici Hrvatskoj - Batelja Lodeta, Kristina; Bolarić, Snježana; Vokurka, Aleš; Kereša, Snježana; Benčić, Đani; Očić, Vesna (2019)
Razvoj ekološkog maslinarstva direktno je povezan sa razvojem ekološke poljoprivrede. Prve zabilježene podatke u EUROSTAT-u o količinama ekološki proizvedenih maslina imamo već 2002. godine za Italiju, da bi se od 2009. godine pratila i Hrvatska. Najveći dio ekološke proizvodnje maslina koncentriran je u Španjolskoj, Italiji i Grčkoj. Zakonodavstvo Europske unije (EU) konstantno se zalaže za stimulaciju i rast proizvodnje ekološke hrane i ekološkog načina proizvodnje. U Hrvatskoj, iako proizvodnja ekoloških maslina ima zabilježen značajan porast prinosa kao i uzgojnih površina, nailazimo na nerazumijevanje i nepoznavanje principa ekološke proizvodnje, neučinkovitu zakonsku regulativu, nepostojanje ekoloških rasadnika kao i vrlo mali broj uljara za preradu ekološki proizvedenih maslina.
In this work, the effectiveness of cold and hot (Soxhlet) extraction of oil from the dry matter of lyophilized olive pastes (without pit and with pit) and seeds of olive fruits of Leccino cultivar, was investigated. The effect of extraction on the content of total phenols and ortho-diphenols in the obtained oils was also investigated. Total phenols content and antioxidant capacity (IC50) were determined in olive pastes and seeds. Cold and hot extraction proved to be equally effective in extracting oil from lyophilized olive pastes, while hot extraction was more efficient in extracting oil from seeds. Olive pastes without pits had the highest total phenols content (12.9 mg g-1 of dry mass) of the three investigated plant materials. Therefore, the oils obtained from them, particularly those obtained by Soxhlet extraction, contained the highest total phenols content (396.7 mg kg-1) and ortho-diphenols (206.3 mg kg-1). Compared to olive pastes, the seeds had a statistically significantly lower total phenols content and a multiple lower antioxidant capacity. The results confirmed that pits removal reduces the negative influence of peroxidases from seeds on the phenol compounds in the olive paste and in the oil, also suggesting that hot extraction increases the solubility of phenols from plant material in the oil.
Bibliografija: str. 19-20.
Sažetak ; Summary.
Keywords: Maslinarstvo -- Ekološka poljoprivreda -- Organska proizvodnja; Europska unija; Hrvatska